PENERAPAN PROGRAM CSR UNTUK MENINGKATKAN PERILAKU PEMBELIAN KONSUMEN PADA RITEL - YULIN, . (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Corporate social responsibility (CSR) is an retailer’s responsibility at environment. There are many of CSR model, but the essesntial of each CSR model is responsibility at environment. The CSR model: cause promotion, cause related marketing, corporate social marketing, corporate philanthropy, community volunteering, dan social resposible business practices. When the retailer applicate the CSR increased retailer’s reputation so the community will be positive respond. The community have usefulness of the CSR application by retailer, so the community will visiting terhadap retailer as a positive respond toward CSR. The buying at the retailer as a real respond from the community. So, the application of CSR will be increased the consumer buying behavior.